Revisiting People’s Involvement in Environmental Impact Analysis Process: A Constitutional Review Towards Sustainable Development - Rasjidi, Ira Thania; Nasution, M. Y. F. Hafidz; Ningrum, Maya Puspita (UNIVERSITAS PAKUAN, 2019)
The protection of environmental and economic rights has been part of the human rights as well as one of the main purposes of sustainable development. However, the drive caused by rapid economic growth have caused the effort in environmental protection to be neglected in the past decades, including in Indonesia. Since 1982, Indonesia has enacted environmental protection regulatory framework, including by adopting the Environmental Impact Analysis (EIA) as the legal instrument in the environmental decision-making process. One of the main characteristics in the EIA process is the people’s involvement as regulated under Law No. 32 of 2009 and its implementing regulations. However, the enforcement of this mandatory obligation only remains as a formal compliance rather than serving the actual purpose. Even worse, the recently enacted Job Creation Law have immensely severed the environmental protection effort by amending the people’s involvement principle into a more restrictive regulatory framework. Therefore, this article is aimed to revisit the current Job Creation Law on the people’s involvement in the EIA Process from a constitutional perspective towards sustainable development.